The molecular conformation, but not disaggregation, of humic acid in water solution plays a crucial role in promoting plant development in the natural environment - Aranaz, Javier; de Hita, David; Olaetxea, Maite; Urrutia, Oscar; Fuentes, Marta; Baigorri, Roberto; Garnica, Maria; Movila, Maria; Zamarreño, Angel M.; Erro, Javier; Baquero, Enrique; Gonzalez-Gaitano, Gustavo; et al. (Frontiers in Plant Science, 2023)
Many studies have shown the capacity of soil humic substances (HS) to improve plant growth in natural ecosystems. This effect involves the activation of different processes within the plant at different coordinated molecular, biochemical, and physiological levels. However, the first event triggered by plant root-HS interaction remains unclear. Some studies suggest the hypothesis that the interaction of HS with root exudates involves relevant modification of the molecular conformation of humic self-assembled aggregates, including disaggregation, which might be directly involved in the activation of root responses. To investigate this hypothesis, we have prepared two humic acids. A natural humic acid (HA) and a transformed humic acid obtained from the treatment of HA with fungal laccase (HA enz). We have tested the capacity of the two humic acids to affect plant growth (cucumber and Arabidopsis) and complex Cu. Laccase-treatment did not change the molecular size but increased hydrophobicity, molecular compactness and stability, and rigidity of HA enz. Laccase-treatment avoided the ability of HA to promote shoot- and root-growth in cucumber and Arabidopsis. However, it does not modify Cu complexation features. There is no molecular disaggregation upon the interaction of HA and HA enz with plant roots. The results indicate that the interaction with plant roots induced in both HA and laccase-treated HA (HA enz), changes in their structural features that showed higher compactness and rigidity. These events might result from the interaction of HA and HA enz with specific root exudates that can promote intermolecular crosslinking. In summary, the results indicate that the weakly bond stabilized aggregated conformation (supramolecular-like) of HA plays a crucial role in its ability to promote plant development. The results also indicate the presence of two main types of HS in the rhizosphere corresponding to those non-interacting with plant roots (forming aggregated molecular assemblies) and those produced after interacting with plant root exudates (forming stable macromolecules).